Routine HIV testing in acute medical admissions in a high prevalence area reduces morbidity and mortality of HIV: a full cycle audit. (June 2016) - Hill-Tout, Rachel; Cormack, Ian; Elgalib, Ali
Late HIV diagnosis in the UK remains a major cause of morbidity and mortality. In line with British HIV Association recommendations, we implemented routine HIV Screening in Croydon University Hospital Acute Medical Unit in London after an audit in 2011 revealed very high levels of late diagnosis. Our re-audit assessed the impact of Acute Medical Unit screening and found that patients identified by screening, compared to those tested due to clinical suspicion of HIV, were significantly less likely to be diagnosed late, had fewer AIDS-defining illnesses and shorter hospital admissions. In addition, screening identified patients who were not in traditional 'high-risk' groups and patients who had defaulted HIV care and who subsequently re-engaged with care.